Between Boundaries, towards Decolonial Possibilities in a Feminist Classroom: Holding a Space between the Qurʾan and the Bible - Seedat, Fatima (Religion & theology, 2020)
Abstract This paper theorises the teaching and learning of feminist approaches to the Bible and the Qurʾan in a Master’s course with a historically Christian focus. It draws on a critical review of an assessment task, and our pedagogical experiences as teachers, to consider how students made meaning within this decolonial pedagogical space, which explored feminist approaches to the two sacred texts. Our analysis shows, our work as teachers was to hold onto the tension in the space between two feminist approaches to sacred texts, and to not succumb to the pressure to release, trivialise or exacerbate that tension.